A climate chamber study on subjective and physiological responses of airport passengers from walking to a sedentary status in summer. (January 2022) - Jia, Xinyu; Cao, Bin; Zhu, Yingxin
Abstract: Passengers usually walk a long distance before arriving at the seating areas of the departure lounge in airport terminals. The current standards for airport terminals have not considered passengers' thermal comfort during the walking status and the variations in thermal comfort with the dwell time during the sedentary period after walking. Therefore, 14 male subjects dressed in 0.57 clo were recruited to simulate passengers in the summer in the climate chamber. The subjects walked for 5 min, 10 min, and 15 min, respectively, at a pace of 1.1–1.2 m/s with a 5 kg bag at 26 °C. Subsequently, they entered the sedentary phase under three conditions with different operative temperatures ( T op ) (23 °C, 26 °C, and 29 °C). Each subject participated in nine experiments. Variations in subjective perceptions and physiological parameters were recorded throughout the study. The summer design parameters for Chinese airport terminals (25–26 °C, 50% RH) did not satisfy the passengers' thermal comfort when the walking time exceeded 10 min. Exponential relationships between neutral T op ( T n ) and time were acquired for the sedentary phase. After walking for 5 min, 10 min, and 15 min, the T n values were 24.0 °C, 21.0 °C, and 18.9 °C, respectively. T n required 17.6–21.0 min to recover to the steady-state sedentary level. Thus, the comfort zones under the current standards may not meet the thermal comfort demands of passengers with short dwell times. Highlights: Three walking times and three T op in sedentary status were involved in this study. The subjective and physiological effects of walking time and T op were analysed. The exponential relationship between neutral Top and sedentary time was obtained. The summer comfort zone in standards may not meet the passengers' thermal comfort.